2018
DOI: 10.1007/s11947-018-2161-y
|View full text |Cite
|
Sign up to set email alerts
|

Feed-Forward Prediction of Product Qualities in Enzymatic Protein Hydrolysis of Poultry By-products: a Spectroscopic Approach

Abstract: Enzymatic protein hydrolysis (EPH) is one of the industrial bioprocesses used to recover valuable constituents from food processing by-products. Extensive heterogeneity of byproducts from, for example, meat-processing is a major challenge in production of protein hydrolysates with stable and desirable quality attributes. Therefore, there is a need for process control tools for production of hydrolysates with defined qualities from such heterogeneous raw materials. In the present study, we are reporting a new f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The composition of the raw materials used in this part of the study is found in Table 2 . The protein, fat, and ash content of CM and MDCR correspond to an earlier study of poultry by-products of Norwegian origin [ 23 ]. Hydroxyproline (Hyp) is found almost exclusively in collagen, and the amount of Hyp is frequently used to estimate collagen contents in tissues [ 24 ].…”
Section: Resultssupporting
confidence: 79%
“…The composition of the raw materials used in this part of the study is found in Table 2 . The protein, fat, and ash content of CM and MDCR correspond to an earlier study of poultry by-products of Norwegian origin [ 23 ]. Hydroxyproline (Hyp) is found almost exclusively in collagen, and the amount of Hyp is frequently used to estimate collagen contents in tissues [ 24 ].…”
Section: Resultssupporting
confidence: 79%
“…Recently, these reactions have been extensively used in various food industries and other biomedical applications. Their use in the agri-food industry promotes proper processing, storage activities and the functionalization of food products [1][2][3][4][5][6]. Enzymes play a significant role in enhancing the safety of food products [7].…”
Section: Introductionmentioning
confidence: 99%
“…With such an approach, Wubshet et al 26 showed the first application of RS as a rapid tool for estimating calcium and ash contents in bone and meat mixtures after mechanical deboning of chicken meat. The same approach was recently also used to characterize chemical variation of poultry by-products fed into a bioprocess 27 and for quantification of collagen contents in ground meat. 5 Moving a wide area RS probe around a sample surface opens the possibility for representative sampling of rather heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%